A case of haemoglobinopathy and elevated HbA1c. (January 2017) - Surchi, Haval; Rea, Rustam
Abstract: A 34‐year‐old woman was referred to the specialist diabetes service for investigation of fainting episodes. She was otherwise fit and well, spending 10 hours a week cycling, running and swimming. Multiple pathology investigations were undertaken prior to her appointment which were all within normal limits except her HbA1c result which was raised at 77 mmol/mol (9.2%). She had no symptoms of hyperglycaemia. Following a review in the diabetes clinic, a suspicion of a spurious HbA1c result arose. Her blood sample was reprocessed using a boronate affinity assay (Alere Afinion analyser) and the result came back as 32 mmol/mol (5.1%) compared with an HPLC (Bio‐Rad D100) method of 83 mmol/mol (9.7%). Further analysis of her haemoglobin (Hb) subtypes showed that she had Hb Wayne. Hb Wayne is a variant haemoglobin first described in 1976 as an elongated α‐chain frame shift variant. It does not produce clinical symptoms and exists as two isoforms: Hb Wayne I (Asn 139) and Hb Wayne II (Asp 139). The prevalence of Hb Wayne trait is unknown; 62 cases over a 16‐year period have been reported in a predominantly US population. The abnormal Hb Wayne haemoglobin acts like HbA1c (even though it is not attached to glucose), and this gives an overlapping peak when the separated species are detected and provides a falsely elevated HbA1c value. Copyright © 2017 John Wiley & Sons.